Predictive Value of the Present-On-Admission Indicator for Hospital-acquired Venous Thromboembolism. Issue 4 (April 2015) - Khanna, Raman R.; Kim, Sharon B.; Jenkins, Ian; El-Kareh, Robert; Afsarmanesh, Nasim; Amin, Alpesh; Sand, Heather; Auerbach, Andrew; Chia, Catherine Y.; Maynard, Gregory; Romano, Patrick S.; White, Richard H.
Abstract : Background: Hospital-acquired venous thromboembolic (HA-VTE) events are an important, preventable cause of morbidity and death, but accurately identifying HA-VTE events requires labor-intensive chart review. Administrative diagnosis codes and their associated "present-on-admission" (POA) indicator might allow automated identification of HA-VTE events, but only if VTE codes are accurately flagged "not present-on-admission" (POA=N). New codes were introduced in 2009 to improve accuracy. Methods: We identified all medical patients with at least 1 VTE "other" discharge diagnosis code from 5 academic medical centers over a 24-month period. We then sampled, within each center, patients with VTE codes flagged POA=N or POA=U (insufficient documentation) and POA=Y or POA=W (timing clinically uncertain) and abstracted each chart to clarify VTE timing. All events that were not clearly POA were classified as HA-VTE. We then calculated predictive values of the POA=N/U flags for HA-VTE and the POA=Y/W flags for non-HA-VTE. Results: Among 2070 cases with at least 1 "other" VTE code, we found 339 codes flagged POA=N/U and 1941 flagged POA=Y/W. Among 275 POA=N/U abstracted codes, 75.6% (95% CI, 70.1%–80.6%) were HA-VTE; among 291 POA=Y/W abstracted events, 73.5% (95% CI, 68.0%–78.5%) were non-HA-VTE. Extrapolating from this sample, we estimated that 59% of actual HA-VTE codes were incorrectly flagged POA=Y/W. POA indicator predictive values did not improve after new codes were introduced in 2009. Conclusions: The predictive value of VTE events flagged POA=N/U for HA-VTE was 75%. However, sole reliance on this flag may substantially underestimate the incidence of HA-VTE. Abstract : Supplemental Digital Content is available in the text.